Limb Ischemia-Related Interventions and 30-Day Mortality After Femoro-Femoral VA-ECMO: A Pre/Post Implementation-Era Comparison - Robert Zilberszac; Andreas Gleiss; Bernhard Richter; Anne-Kristin Schäfer; Julia Riebandt; Patrick Haider; Thomas M. Hofbauer; Max Lenz; Georg Gelbenegger; Yalong Sun; Daniel Nöstlinger; Christian Hengstenberg; et al. (Journal of Clinical Medicine, 2026)
Background/Objectives: Femoro-femoral veno-arterial extracorporeal membrane oxygenation (VA-ECMO) is associated with limb ischemic complications. Routine near-infrared spectroscopy (NIRS) monitoring and a more standardized distal perfusion strategy were introduced at our institution in 2016. We compared ischemia-related interventions, amputations, and early mortality between the treatment eras. Methods: Consecutive patients undergoing femoro-femoral VA-ECMO from 2012 to 2024 were analyzed retrospectively and stratified by VA-ECMO initiation before 2016 or from 2016 onward. The primary endpoint was a peripheral ischemic vascular complication requiring surgical or interventional therapy; an inclusive sensitivity definition additionally incorporated four clinically plausible but less certain events. Period-specific rates were estimated using Poisson regression adjusted for baseline distal perfusion cannula (DPC) status and extracorporeal cardiopulmonary resuscitation (eCPR). Results: The analytic cohort comprised 270 patients (45 pre-2016 and 225 post-2016). The primary endpoint occurred in 50 patients (18.5%, 95% confidence interval (CI) 14.1–23.7): 3/45 (6.7%, 95% CI 1.4–18.3) before 2016 and 47/225 (20.9%, 95% CI 15.8–26.8) thereafter. Adjusted rates were 4.6% (95% CI 1.0–20.5) and 18.9% (95% CI 13.6–26.3), with an adjusted risk ratio of 4.11 (95% CI 1.06–17.93). The inclusive sensitivity analysis yielded similar estimates (adjusted risk ratio 3.31, 95% CI 1.05–11.47). Five patients underwent lower-limb amputation (1/45 pre-2016 and 4/225 post-2016). Kaplan–Meier 30-day mortality estimates were 56.8% overall (95% CI 50.8–62.9), 58.9% pre-2016 (95% CI 44.9–73.5), and 56.4% post-2016 (95% CI 49.9–63.1). Conclusions: Ischemia-related interventions were more frequently recorded after 2016, while amputations remained rare and 30-day mortality was similar. Because monitoring, DPC practice, and other aspects of care changed concurrently, and NIRS was used without a standardized trigger algorithm, the reasons for the observed era difference cannot be determined. The findings are exploratory and do not establish causal effects of NIRS or DPC use.